PENGEMBANGAN WILAYAH KABUPATEN SIDOARJO SEBAGAI WILAYAH PINGGIRAN KOTA METROPOLITAN SURABAYA DAN MOBILITAS PENDUDUK - Adika, I Nyoman (PIRAMIDA, 2012)
The physical and functional development restructuring program in Surabaya due tospace limitation has caused a development overflowing beyond the city toward Surabaya-Malang corridor. One of regions in that corridor is Sidoarjo Regency. The increase ofeconomic activities due to the development overflowing to Sidoarjo comes together with theraise of labor mobility to the region.Related to the problem mentioned before, this research aims to (1) analyze physicaland functional development growth and its distribution in Sidoarjo Regency during the lastdecade as the impact of internal restructuring program in Surabaya; (2) analyze the role ofSidoarjo Regency in endeavoring to stabilize environment of Surabaya City; (3) analyze theimpact of physical and functional development in Sidoarjo Regency on the inflow of formaland informal sectors labors and to identify their origins; and (4) identify factors causinginformal sector labor migrant tend to choose Sidoarjo Regency as a place to earn living aswell as the mobility pattern, and to what extent Sidoarjo Regency can serve as a steppingstone for them to initiate their businesses.The results show that (1) the pro natal population policy held by Old OrderGovernment has increased birth numbers and pushed population growth dramatically; (2)capital investment during the New Order that tend to be concentrated in big cities, likeJakarta and Surabaya has caused huge people mobility to the cities. This inflow of lowskilled and educated migrant to big cities would create new problems, not only that ofrelated to physical, but also to the social capacity; and (3) area limitation in cities causesthe development goes beyond neighborhood areas. The development overflowing fromSurabaya to Sidoarjo could decrease population growth of Surabaya, and on the otherhand, the population growth of Sidoarjo increases considerably. The process of“kotadesasi” in Sidoarjo Regency has soundly occurred because the farmers there haveinvolved in agricultural industry since long time, like shrimp crackers, handicraft, case andbags industries. Based on the results, two recommendations can be oferred, (1) each citygrowth will reach a full period, therefore a counterpart area will be necessary to receivethe overflowing from a fully developed city; and (2) development program must bedecentralized in order to distribute people mobility.
Keywords: development overflowing, pro-natal, people mobility, decentralization